2004
DOI: 10.1097/00005721-200407000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Working Women’s Breastfeeding Experiences

Abstract: These findings can help nurses and other healthcare professionals in providing anticipatory guidance to women who plan to continue breastfeeding after returning to work. Further research should investigate the relationship between psychological distress, work productivity, family functioning, and breastfeeding activities of working women who breastfeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 17 publications
1
52
0
3
Order By: Relevance
“…10,11 A recent series of meta-analyses of the evidence on the effects of breastfeeding on infant health in developed countries concluded that breastfeeding is associated with a reduced risk of many diseases in both mothers and their infants. 12 Extant literature documents the difficulties faced by mothers returning to the workplace, 13 provides advice to mothers who wish to combine paid work and breastfeeding, [14][15][16][17] provides advice to companies that wish to promote breastfeeding, [18][19][20][21] and describes individual workplaces that have successfully promoted breastfeeding among employed mothers. 19,22,23 Policy statements and recommendations concerning the successful combination of maternal work and breastfeeding encourage directly feeding the infant from the breast either as a preferred accommodation 2,24 or as one of several possible accommodations.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 A recent series of meta-analyses of the evidence on the effects of breastfeeding on infant health in developed countries concluded that breastfeeding is associated with a reduced risk of many diseases in both mothers and their infants. 12 Extant literature documents the difficulties faced by mothers returning to the workplace, 13 provides advice to mothers who wish to combine paid work and breastfeeding, [14][15][16][17] provides advice to companies that wish to promote breastfeeding, [18][19][20][21] and describes individual workplaces that have successfully promoted breastfeeding among employed mothers. 19,22,23 Policy statements and recommendations concerning the successful combination of maternal work and breastfeeding encourage directly feeding the infant from the breast either as a preferred accommodation 2,24 or as one of several possible accommodations.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Other independent variables include age of infant when the mother returned to work, work characteristics, and characteristics likely to be related to breastfeeding duration or to combining work and breastfeeding, including attitudes toward breastfeeding, belief in the benefits of breastfeeding, 13 and personal goals for exclusive or total breastfeeding duration. 19 Exclusive breastfeeding goal was used in the intensity analysis, and total breastfeeding goal was used in the duration analysis.…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…5 Employers may influence the work climate of breastfeeding support by either adhering to or ignoring company policies, informally supporting or discouraging breastfeeding employees, or managing or disregarding issues arising among coworkers. [6][7][8] Breastfeeding provides unique health advantages to both the infant and mother, 9 and thus a breastfeeding-friendly workplace for the employed mother is recommended to increase the initiation and duration of breastfeeding. [10][11][12][13] In a breastfeeding-friendly workplace/policy, the provision of lactation rooms and breast-pumping breaks for female employees to express breastmilk for their infants is a critical element and may increase a mother's intention to continue breastfeeding after returning to work.…”
Section: Introductionmentioning
confidence: 99%
“…Le moment de la décision d'allaiter est un facteur d'influence important sur le comportement d'allaitement des mères [9] : plus la décision est précoce, meilleures seront [10] Confiance en soi, sentiment d'auto-efficacité [10,24] Absence de difficultés d'allaitement [13] Cohabitation mère/bébé 24 h/24 à la maternité [11] Être plus jeune, seule, de plus faible statut socioéconomique, récemment immigrée, avoir déménagé en raison de la naissance du bébé [9,11,13,16,17] Expérience passée négative d'allaitement [9] Ambivalence ou non désir d'allaiter, décision tardive Manque d'informations sur la durée optimale [17] Perception d'une insuffisance de lait, incertitude concernant la quantité de lait prise [9,10,13,[16][17][18] Peu de confiance en soi, gêne d'allaiter en public, dépression postnatale [11,24,25] Expérience initiale négative, difficultés d'allaitement [21] Tétine précoce au bébé [12,22] Obésité, tabagisme [10,12,[28][29][30] Emploi de la mère (> 20 h/semaine) [12,14,31] Facteurs liés au bébé et à son état de santé Technique de succion correcte Faible prise de poids du bébé [9,32] Problème de succion [17] Facteurs liés à l'entourage Soutien émotionnel de l'entourage Soutien du partenaire, partenaire favorable à l'allaitement [12,40] Soutien téléphonique des paires …”
Section: Facteurs De Choix Personnel (Intentions Motivations Décisiunclassified
“…Les mères qui continuent à fumer pendant leur grossesse et après la naissance ont 2,18 fois plus de chances de ne plus allaiter à dix semaines, par rapport aux mères non fumeuses [30]. [12,31].…”
Section: Pratique De L'allaitement Et Des Soins Au Bébéunclassified